Efektivitas Program Same Day Services Pasang Baru dan Perubahan Daya Listrik di PT PLN (Persero) Unit Layanan Pelanggan (ULP) Jatibarang - Ulfatillah Salmi; Ertien Rining Nawangsari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The increasing need for electricity is part of the public interest. The availability of electricity must continue to be ensured to support all forms of activity, such as the economy. The government, through PT PLN (Persero), is responsible for distributing electrical energy to remote areas of the country quickly, easily and safely for the community. Based on this, PT PLN (Persero) is trying to provide electricity to the community quickly through the Same Day Services (SDS) Program for New Installation and Power Change. This program is expected to be a breakthrough in responding to the increasing demand for electricity needs of the community over time. Therefore, the aim of this research is to find out how effective the Same Day Services (SDS) New Installation and Electric Power Change Program implemented by PT PLN (Persero) on Customer Service Unit (ULP) Jatibarang. The research method used is descriptive qualitative research. The data taken is based on the results of observations, interviews, documentation, as well as reviewing data sourced from PT PLN (Persero) ULP Jatibarang documents, articles and other news that are relevant to the research topic. The results of this research show that the SDS Program at ULP Jatibarang shows positive results from several effectiveness indicators according to Budiani. Thus, the author concludes that this program has been running effectively.